Implikasi Hukum Terhadap Anak Yang Berhadapan Dengan Hukum Yang Disebabkan Faktor Broken Home - Revi Yana; Ceren Falah Al juvani; Muhammad Zul Hilmi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The family is the first and foremost environment in shaping a child's personality. When the family structure is disrupted due to divorce or severe conflict between parents, the child is the most psychologically affected. This case study highlights the story of a family with two children who experienced family dysfunction (broken home) due to passive and violent behavior from the father figure, and its impact on the psychology of the children. The findings show that this condition has a significant impact on mental health, social behavior, and the tendency of children to commit crimes as a form of escape from emotional stress.